(3ehgHI GdQMef aj JaSjQ GdbQBfs - (3eMeO QVG Hf bGSe Hf eMeO GdZQGhj, J (B1385(3g` (B1965(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj gOGfG dgPG heG cfG dfgJOj dhdG Cf gOGfG Ydi dSGf GfHjGFg (B... (3hMjK Cf ShQ GdcJGH GdTQja efgG ecj heOfj hHYVgG Chd fRhdg aj ecI hJeGeg jchf aj GdeOjfI ade GJYQV dPcQ Pdcs
(3BNQgG (B:s
(3BNQgG(B: (3GdfGS, (B... (3bhdg GdhShGS GdehShS, dG faS GdhShSI GdhGbYI ef GdLf, bhdg GdNfGS, GdPj YGOJg Cf jJCNQ hjScf EPG PcQ GdEfSGf hGSe GdTjWGf GdPj jdbj GdhShSI aj UOhQ GdfGS(B... (3bhdg hGdfS(B: (3Hfj BOe(B. ... (3hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3GdPQjYI, L (B23: 175s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs